Enhancing the utility of virtual surgical pre-assessment. - Goonasekera, Chulananda; Gammon, Nicola; Found, Phil; Sheikh, Asme; Fleming, Ian; Amoako, Derek; Nanavati, Nilesh (British Journal of Nursing, 2021)
During the COVID-19 pandemic, virtual pre-assessment was introduced for all elective and semi-urgent surgeries to maintain surgical clinical services in the authors' Trust. This mainly involved telephone pre-assessments, although occasionally video technology was used. This had to be managed and maintained at a distance with little or no training or established method. This article includes experiences of staff involved in a single tertiary centre, an assessment of the pros and cons of virtual pre-assessment and concludes with a set of recommendations to enhance the utility of the service for the future.